Relationships among Verbal Memory, Spatial Working Memory and Intelligence in Children of 10-11 years - Burdukova Yu,A; Alekseeva O.S; Chizhova B.A; Shcheglova A.V (Moscow State University of Psychology and Education, 2018)
The issue investigates the relationship Selective Reminding Test (SRT), a test of spatial working memory (SWM) with Kaufman Assessment Battery for Children (KABC II). It has been found that the efficiency of memorizing verbal material is associated with the estimates on the K-ABC Sequential processing scale and K-ABC Simultaneous processing scale, but not to the Learning scale of education, is measured indirectly verbal memorization. Spatial working memory is not related to IQ.The issue is part of a research project on cognitive function in children with neuro-oncological disorders